2011
DOI: 10.1021/ja208669s
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide-Induced N–N Bond Cleavage of Nitrous Oxide That Is Competitive with Oxygen Atom Transfer to Carbon Monoxide As Mediated by a Mo(II)/Mo(IV) Catalytic Cycle

Abstract: In the presence of CO, facile N-N bond cleavage of N(2)O occurs at the formal Mo(II) center within coordinatively unsaturated mononuclear species derived from Cp*Mo[N((i)Pr)C(Me)N((i)Pr)](CO)(2) (Cp* = η(5)-C(5)Me(5)) (1) and {Cp*Mo[N((i)Pr)C(Me)N((i)Pr)]}(2)(μ-η(1):η(1)-N(2)) (9) under photolytic and dark conditions, respectively, to produce the nitrosyl, isocyanate complex Cp*Mo[N((i)Pr)C(Me)N((i)Pr)](κ-N-NO)(κ-N-NCO) (7). Competitive N-O bond cleavage of N(2)O proceeds under the same conditions to yield the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 26 publications
4
32
0
Order By: Relevance
“…93 The reaction product can be isolated and is stable as a solid if stored at À35 1C. 98,99 The formation of stable covalent adducts of N 2 O can be achieved without transition metals. Apart from an alkylation reaction with MeO 3 SCF 3 (O-and b-N-alkylation), it was shown that the complex can be reduced to give a stable radical anion.…”
Section: N 2 O As N-atom Donormentioning
confidence: 99%
“…93 The reaction product can be isolated and is stable as a solid if stored at À35 1C. 98,99 The formation of stable covalent adducts of N 2 O can be achieved without transition metals. Apart from an alkylation reaction with MeO 3 SCF 3 (O-and b-N-alkylation), it was shown that the complex can be reduced to give a stable radical anion.…”
Section: N 2 O As N-atom Donormentioning
confidence: 99%
“… 9 Sita and co-workers developed a homogeneous version of this transformation, mediated by the Mo( ii ) complex, Cp*Mo(NCN)(CO) 2 (NCN = i PrNC(Me)N i Pr). 10 In this process, N 2 O oxidizes Cp*Mo(NCN)(CO) 2 to form a Mo( iv ) oxo, Cp*Mo(NCN)(O), which then reacts with CO to form CO 2 and regenerate Cp*Mo(NCN)(CO) 2 . However, an N–N bond cleavage reaction, which results in irreversible formation of Cp*Mo(NCN)(NCO)(NO), was found to be competitive with oxo formation.…”
Section: Introductionmentioning
confidence: 99%
“…8 An additional example has a molybdenum(II) dicarbonyl form an isocyanate concomitant with N 2 O cleavage. 9 In all these examples, however, the nitrogen source is an azide or N 2 O. Two examples of (µ 2 ,η 1 ,η 2 -N 2 )Hf 2 complexes show N 2 cleavage that is facilitated by reduction with CO to form an equivalent of isocyanate for each mole of N 2 (Fig.…”
Section: Introductionmentioning
confidence: 99%